Spectral and timing properties of IGR J00291+5934 during its 2015 outburst. Issue 3 (22nd December 2016) - Sanna, A.; Pintore, F.; Bozzo, E.; Ferrigno, C.; Papitto, A.; Riggio, A.; Di Salvo, T.; Iaria, R.; D'Aì, A.; Egron, E.; Burderi, L.
Abstract: We report on the spectral and timing properties of the accreting millisecond X-ray pulsar IGR J00291+5934 observed by XMM–Newton and NuSTAR during its 2015 outburst. The source is in a hard state dominated at high energies by a Comptonization of soft photons (∼0.9 keV) by an electron population with kT e ∼ 30 keV, and at lower energies by a blackbody component with kT ∼ 0.5 keV. A moderately broad, neutral Fe emission line and four narrow absorption lines are also found. By investigating the pulse phase evolution, we derived the best-fitting orbital solution for the 2015 outburst. Comparing the updated ephemeris with those of the previous outbursts, we set a 3σ confidence level interval −6.6 × 10 −13 s s −1 $< \dot{P}_{{\rm orb}} < 6.5 × 10^{-13}$ s s −1 on the orbital period derivative. Moreover, we investigated the pulse profile dependence on energy finding a peculiar behaviour of the pulse fractional amplitude and lags as a function of energy. We performed a phase-resolved spectroscopy showing that the blackbody component tracks remarkably well the pulse profile, indicating that this component resides at the neutron star surface (hotspot).